2022
DOI: 10.22207/jpam.16.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Optimization Studies of Bacterial Pigments

Abstract: Recent concern for human safety and environmental protection has rekindled interest in natural pigment sources. In comparison to synthetic pigments, microbial pigments show better biodegradability and environmental compatibility and are used in a variety of applications ranging from food to cosmetics. The areas of attention for economical pigment synthesis include the identification of novel microbiological sources and improvement of process parameters. The purpose of this research was to screen and identify m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…indicated a favorable effect of inoculum concentration on pigment generation, peaking at 2 g/L. 43 This aligns with our optimization findings, reinforcing the notion that this specific inoculum concentration supports rapid mycelial growth, ultimately enhancing pigment and antioxidant metabolite production. 45 In the case of G. alkanivorans strain 1B, Fernandes et al (2018) found that the stress experienced by the strain was pivotal for carotenoid production, particularly under prolonged exposure to light at varying lux levels (400-3000 lux after 19 days).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…indicated a favorable effect of inoculum concentration on pigment generation, peaking at 2 g/L. 43 This aligns with our optimization findings, reinforcing the notion that this specific inoculum concentration supports rapid mycelial growth, ultimately enhancing pigment and antioxidant metabolite production. 45 In the case of G. alkanivorans strain 1B, Fernandes et al (2018) found that the stress experienced by the strain was pivotal for carotenoid production, particularly under prolonged exposure to light at varying lux levels (400-3000 lux after 19 days).…”
Section: Discussionsupporting
confidence: 87%
“…These variables directly impact the maximization or limitation of desired metabolites, emphasizing the importance of identifying and optimizing the right combination of culture conditions. 43 As a result, the fermentation process of actinomycetes for pigment and antioxidant production is intricate. It greatly depends on yield, culture medium, and inoculum and necessitates specific environmental conditions pH, temperature, and stirring speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical parameters of bacterial pigment production : The pigmented colony underwent incubation at temperatures (25-40°C) and pH (4-14) for 24 hours, yielding maximum pigment production, assessed via OD at 425nm. UV exposure (30sec-5min) followed by 37°C incubation for 24 hours induced mutations, enhancing pigment production, measured similarly (Fatima et al, 2022) (Fatima Shatila et al, 2013).…”
Section: Methodsmentioning
confidence: 96%
“…It is very important to investigate the potential of microbial pigment, to use it in various industries. The antimicrobial activity of the pigment is tested by antibacterial and antifungal assay 5 . Both gram positive and gram-negative bacteria are susceptible to antimicrobial effects of bacterial pigment 6 .…”
Section: Introductionmentioning
confidence: 99%